Clinicopathological study of sinonasal tract lesions - Naseer, Shifa Mariam Abdul; Bhosle, Smita; Ingin, Rajashree J (Journal of Pathology of Nepal, 2025)
Background: The sinonasal tract is a histologically complex structure, resulting in a wide spectrum of non-neoplastic and neoplastic lesions encountered in clinical practice. Though presenting clinical features and imaging techniques help to reach a presumptive diagnosis, histopathological examination remains the mainstay for definitive diagnosis and appropriate management. This study aimed to examine the histopathological spectrum of sinonasal tract lesions, diagnosed as per the World Health Organization 2022 classification of tumours of the nasal cavity and paranasal sinuses, and correlate histopathological findings with clinical presentation.Material and Methods: This was a five-year study (3-year retrospective and 2-year prospective study) conducted from January 2020 to December 2024 at the Department of Pathology, Gulbarga Institute of Medical Sciences, Kalaburagi, Karnataka, India. Relevant clinical features, histopathological diagnoses, and classification were recorded.Results: A total of 151 cases of sinonasal tract lesions were included, neoplastic lesions constituted 125 (83%) cases, and neoplastic lesions accounted for 26 (17%). Nasal obstruction was the most common presenting symptom. Inflammatory polyp was the most common non-neoplastic lesion, followed by fungal sinusitis. Benign tumours (15%) constituted sinonasal papilloma, capillary hemangioma, schwannoma, cemento-ossifying fibroma, and pleomorphic adenoma. Malignant neoplasms (2%) included olfactory neuroblastoma, squamous cell carcinoma, and adenoid cystic carcinoma. Clinicopathological correlation was achieved in 77.4% cases.Conclusions: An integrated clinicopathological approach and awareness of a diverse variety of histopathological lesions is vital for categorizing sinonasal tract lesions. Histopathological analysis is crucial for appropriate patient management.